REDUKSI RUGI-RUGI PENSAKLARAN PADA KONVERTER DC-DC ZETA DENGAN TEKNIK ZERO VOLTAGE TRANSITION - Anung -; Givy Devira Ramady; Muchamad Sobri Sungkar; Yoddy Agung Nuhgraha; Agung Wirjawan (Power Elektronik : Jurnal Orang Elektro, 2023)
This paper presents a dc-dc ZETA converter with reduced switching loses at the main switch. Reducing switching loses is obtained by application of a resonance switch, where turn-on by the zero voltage and rising voltage at turn-off is limited by capacitor that it’s placed parallel with main switch. The operational principle of the proposed dc-dc ZETA converter with reduced switching loses has been analyzed under different modes of switching operation. To validate the proposed converter, the implementation is carried out using PSIM software. Simulation result shows that the main switch turn-on at the zero voltage and turn-off at the main switch voltage increase in a quadratic function, so that the result of the voltage and current multiplying is lower, on the other hand the loses of the main switch can be reduced.